THE INOVASI MODEL-MODEL PEMBELAJARAN BAHASA ARAB - Rahma Ramadhani; Taufik (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
Innovation is an important process for human progress in various fields. By innovating, we can create something new and better, and solve problems faced by humans. In a learning system, implementing innovation is something that is emphasized or required. Because with innovation in learning it will be more meaningful and enjoyable for students so that effective and efficient learning can be created. Effective learning models include those based on individual and differentiated approaches, based on Information and Communication Technology (ICT), and based on active and creative approaches. Teachers need to choose a learning model that is appropriate to the learning objectives so that students can achieve their maximum learning potential. Innovation in Arabic language learning models is an important effort to improve the quality of learning and student learning outcomes.